Safety, Tolerability and Pharmacokinetic-Pharmacodynamic Relationship of NX210c Peptide in Healthy Elderly Volunteers: Randomized, Placebo-Controlled, Double-Blind, Multiple Ascending Dose Study - Annette Janus; Daniël Dumas; Juliette Le Douce; Sébastien Marie; Giuseppe Pasculli; Pauline Bambury; Sighild Lemarchant; Philip Kremer; Yann Godfrin (Neurology and Therapy, 2024)
Abstract Introduction Blood-brain barrier (BBB) integrity is fundamental to brain homeostasis, enabling control of substance exchange and safeguarding neurons against harmful toxins, pathogens, and immune cells that lead to dysregulation and inflammation involved in ageing and neurodegenerative diseases (NDD). The cyclized peptide NX210c is a thrombospondin type 1 repeat analogue derived from subcommissural organ-spondin. It exerts beneficial effects in animal models of NDD owing to its effects on neurons and endothelial cells. NX210c demonstrated a good safety profile in a single ascending dose phase 1a clinical study. The present multiple ascending dose phase 1b study was performed to evaluate the tolerability and pharmacological effects of repeated doses of NX210c in healthy elderly (age: > 55 years) volunteers. Methods This was a randomized, placebo-controlled, double-blind study (EudraCT No. 2022-002868-76), investigating safety/tolerability, pharmacokinetics, and pharmacodynamics (including blood and cerebrospinal fluid biomarkers). Participants received 5 or 10 mg/kg NX210c or placebo (10-min infusion) thrice weekly for 4 weeks in an ascending dose fashion. Follow-up was conducted 2 weeks after last dosing. Results The investigation included 29 participants. No serious adverse events were recorded and all adverse events were mild. Dedicated central nervous system testing did not reveal neurotoxicity. Biomarker evaluation showed a statistically significant reduction in blood claudin-5 and a trend toward reduction of blood homocysteine. In silico data modelling revealed salient pharmacokinetic-pharmacodynamic relationships, including reduction of claudin-5, neurofilament light chain, and SPARC-like protein 1 release, and degradation of homocysteine. Conclusion Multiple doses of NX210c exhibited a good safety profile, showed non-cumulative pharmacokinetics, and exerted pharmacodynamic effects on biomarkers linked to BBB integrity. The effects of NX210c on claudin-5 and biomarkers influencing BBB integrity—and the overarching brain protection it offers—provide a novel therapeutic strategy targeting an underlying driver of neurodegenerative conditions for which disease-modifying treatments are limited or not available.